Covert Electromagnetic Nanoscale Communication System in the Terahertz Channel - Ahmed, Areeb; Savacı, Ferit Acar; Savacı, Ferit Acar; Ahmed, Areeb (World Scientific Publishing, 2020)
In this paper, an electromagnetic nano random communication system (EM-nRCS) has been proposed which ensures covert communication in the terahertz (THz) band. In the proposed system, the skewed alpha-stable noise shift keying method has been used to transmit random noise signals (RNSs) from the nano-transmitter (NT) by utilizing single-walled/carbon nanotubes-based true random number generator (SWCNTs-TRNG) and a graphene-based nano-antenna. A line-of-sight THz transparency window between 0.1 THz and 0.5 THz in the THz channel with spreading loss, molecular absorption loss and molecular absorption noise has been considered. Due to the broadband nature of the RNSs, the proposed EM-nRCS provides efficient transmission by overcoming the high path loss and intense channel noise arising from random fluctuations in the THz band. Non-coherent nano-receiver (NR) consisting of the modified extreme value method (MEVM) estimator has been proposed to extract the hidden binary information in the received RNSs. The bit error rate performance shows that the proposed EM-nRCS ensures high performance and covertness for future EM nanoscale communication devices.
Keywords: Random communication systems; Alpha-stable noise; Terahertz band; Transparency window